Perancangan Key Performance Indicators (KPI) Menggunakan Metode Performance Prism (Studi Kasus di Batik Putra Bengawan) - Murman Budijanto; Yusuf Priyandari; Santi Embun Sari (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2012)
The research is aim to design the Key Performance Indicators (KPI) using Performance Prism Method with a case study of a batiks production house namely Batik Putra Bengawan. The research might assist the Batik house to translate the stakeholders’ satisfactions and contributions into organization objectives, strategies, business processes and capabilities. The level of achievement in each factor could be indicated through several performance indicators (PI). Then the importances of the stakeholders’ concern, organization objectives and the PI are measured using a concept that could accommodate a linkage among them namely the Analytical Hierarchy Process (AHP). By doing so, the KPI might be set based on the ten most importance PI such that the performance improvement could be done effectively. This PI design indicates the 25 PI spread over 12 objectives, 23 strategies, 19 business processes, 19 capabilities and includes six stakeholders. The importances wighted using AHP shows that the stakeholder employee has the highest importance and the community gets lowest importance level. The ten most importance PI are choosen as the KPI of the Batik Putra Bengawan. These are the employee productivity, the order fulfillment, the net profit margin, the absentism, number of loyal customers, the bonus receivers among employees, the ratio of new customers, the feedback periods, the consumers’ satisfaction index and the ratio of defect products.